2011
DOI: 10.1002/lary.22180
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the AKT pathway inhibits metastasis in an orthotopic model of head and neck squamous cell carcinoma

Abstract: Introduction Merck's MK-2206 is an orally active, allosteric inhibitor of AKT; a component of the phosphatidylinositol-3 kinase (PI3K) pathway. The PI3K-AKT pathway is a downstream signaling pathway that has recently been found to play an important role in head and neck squamous cell carcinoma (HNSCC). Here we examine the role AKT inhibitors may play in preventing metastasis in HNSCC. Methods Cell migration after 24 hour treatment with sub-therapeutic doses of MK-2206 was assessed using an ELISA assay in 4 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
2
37
0
1
Order By: Relevance
“…Akt activation occurs by phosphorylation at T308 and S473 residues and has been validated as a critical step in the initiation and maintenance of metastatic tumors [47]. Chemical interaction of Akt is reported to cause apoptosis, and inhibit chemotaxis and migration FaDu cells in vitro [48]. When treated with deltonin, downregulated levels both dephosphorylated Akt at Ser473 and p-mTOR at s2448 were found in FaDu cells ( Figure 5C and 5D), suggesting a profound effect of deltonin on Akt/mTOR signaling network in FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation occurs by phosphorylation at T308 and S473 residues and has been validated as a critical step in the initiation and maintenance of metastatic tumors [47]. Chemical interaction of Akt is reported to cause apoptosis, and inhibit chemotaxis and migration FaDu cells in vitro [48]. When treated with deltonin, downregulated levels both dephosphorylated Akt at Ser473 and p-mTOR at s2448 were found in FaDu cells ( Figure 5C and 5D), suggesting a profound effect of deltonin on Akt/mTOR signaling network in FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of AKT fall into two classes: catalytic inhibitors, which compete for the ATP-binding site, and allosteric inhibitors, which act away from this catalytic site. Subtherapeutic doses of the allosteric AKT inhibitor MK-2206 have been shown to significantly reduce cell migration in the FaDu model, with 100% survival of treated mice after 2 weeks compared with 70% survival in a control group (p < 0.05) [58]. Another study demonstrated a synergistic effect of MK-2206 and paclitaxel in combination in SCCHN cell lines through an interaction with autophagy trafficking, leading to increased apoptosis [59].…”
Section: Akt Inhibitionmentioning
confidence: 99%
“…AKT/mTOR/S6K1 is the major antiapoptotic pathway that can confer the survival advantage and also mediate the resistance of HNSCC cells against various chemotherapeutic agents (27,28). We therefore investigated whether garcinol can downregulate the constitutive AKT/mTOR/ S6K1 activation in HNSCC cells.…”
Section: Garcinol Inhibits Akt/mtor/p70s6k Pathway In Hnscc Cellsmentioning
confidence: 99%